The Effects of the CTRT Guidance Group Module on Career Exploration and Career Decision-Making Based on Students` Gender - Shukree Yusof; Ahmad Jazimin Jusoh (Peneliti.net, 2023)
This study aimed to assess the effects of the CTRT Guidance Group Module based on the social cognitive career theory in Career Exploration and Decision-Making for Male and Female Students. The study used a quasi-experimental approach with a pre and post-test control group structure. The experimental design of the research included pre and post-testing. There were 90 students of secondary schools in Malaysia involved in this study. The Career Exploration Service-Revised (CESR) and Career Decision Difficulties Questionnaire-Reverse (CDDQR) questionnaires were used to gather data. Throughout the experimental procedure, the experimental group met weekly between 2.30 and 4.00 p.m. for eight weeks, whereas the control group did not. The study determined that the experimental group students had significantly higher mean scores on CESR and CDDQR questionnaires than the control group students. In light of the relevant research, the impact of the CTRT Guidance Group Module designed for Career Exploration and Career Decision-Making on Student Gender was discussed.